2017
DOI: 10.1111/jtxs.12266
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of the stick‐slip phenomenon in “oral” tribological texture evaluation

Abstract: Dynamic spectral analysis has been applied for the first time to the force-displacement curves in "oral" tribology. Analyzing the stick-slip phenomenon in the dynamic friction provides new information that is generally overlooked or confused with machine noise and which may help to understand friction-related sensory attributes. This approach allows us to differentiate samples that have similar friction coefficient, but are perceived differently in the mouth. The next step of our research will be to combine sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…108 The stick-slip effects could be responsible for vibrations detected by the mechanoreceptors in the mouth, which influence mouthfeel. 109 It has been reported that PRPs can be adsorbed to the dental enamel and can be affected by tannins, leading to the roughening of the dental pellicle and to the sensation of 'rough teeth'. 110 Mechanism III: interaction with oral epithelial cells A third hypothesis about the astringency mechanism suggests the interaction between tannins and oral epithelial cells (Fig.…”
Section: Mechanism Ii: Activation Of Mechanoreceptorsmentioning
confidence: 99%
“…108 The stick-slip effects could be responsible for vibrations detected by the mechanoreceptors in the mouth, which influence mouthfeel. 109 It has been reported that PRPs can be adsorbed to the dental enamel and can be affected by tannins, leading to the roughening of the dental pellicle and to the sensation of 'rough teeth'. 110 Mechanism III: interaction with oral epithelial cells A third hypothesis about the astringency mechanism suggests the interaction between tannins and oral epithelial cells (Fig.…”
Section: Mechanism Ii: Activation Of Mechanoreceptorsmentioning
confidence: 99%
“…30 publications are included in further discussion below). Rotating ball on three‐fixed plates/pins using the Rheo‐tribocell attachment for the modular compact rheometer (MCR) rheometers (Anton Paar, Gratz, Austria) (Baier et al, ; Biegler, Delius, Käsdorf, Hofmann, & Lieleg, ; Carvalho‐da‐Silva, Van Damme, Taylor, Hort, & Wolf, ; Kieserling, Schalow, & Drusch, ; Kim, Wolf, & Baier, ; Krzeminski, Wohlhuter, Heyer, Utz, & Hinrichs, ; Pondicherry, Rummel, & Laeuger, ; Sonne, Busch‐Stockfisch, Weiss, & Hinrichs, ; Steinbach, Guthrie, Smith, Lindgren, & Debon, ). Ring on plate tribo‐rheometry using the Discovery Hybrid Rheometer (TA Instruments) on a rough plastic surface of 3 M Transpore Surgical Tape 1527‐2 (3 M Health Care). (Ng, Nguyen, Bhandari, & Prakash, ; Nguyen, Bhandari, & Prakash, ). Optical tribometer configuration (Dresselhuis et al, ; Dresselhuis, de Hoog, Stuart, & van Aken, ; Liu, Stieger, et al, ; Liu, Stieger, van der Linden, & van de Velde, ). Double‐ball‐on‐plate apparatus attached to MCR rheometers (Goh, Versluis, Appelqvist, & Bialek, ; Joyner et al, ; Joyner, Pernell, & Daubert, ; Joyner, Pernell, & Daubert, ). Plate on three balls (based on a modified texture analyzer (TA‐XT2, TA Instruments) (Chen, Liu, & Prakash, ; Morell, Chen, & Fiszman, ; Sanahuja, Upadhyay, Briesen, & Chen, ), including consideration for stick–slip (Sanahuja et al ()). High frequency reciprocating rig (HFRR) PCS Instrument UK (Tsui, Tandy, Myant, Masen, & Cann, ), and reciprocating pin‐on‐disk (TriboLab, Bruker, Germany) (van Stee, de Hoog, & van de Velde, ). Rotating shaft with sliding bar (de Hoog, Prinz, Huntjens, Dresselhuis, & van Aken, ; Prinz, de Wijk, & Huntjens, ).…”
Section: Soft‐tribology Measurement Systemsmentioning
confidence: 99%
“…These stick-slip patterns may be attributed to the fact that cheese contains both hydrophobic and hydrophilic compounds, which could be coming at the interface interchangeability to cause variation in friction factors. Studies have reported that such stick-slip events could provide important information on the mouthfeel of food materials (Sanahuja et al 2017). Interestingly, no pronounced sudden increase and decrease in friction coefficient was observed for the PepA samples compared with the control samples.…”
Section: Coefficient Of Friction (µ)mentioning
confidence: 82%
“…Studies have reported that such stick‐slip events could provide important information on the mouthfeel of food materials (Sanahuja et al . 2017). Interestingly, no pronounced sudden increase and decrease in friction coefficient was observed for the PepA samples compared with the control samples.…”
Section: Resultsmentioning
confidence: 99%